Differential expression of argininosuccinate synthetase in serous and non‐serous ovarian carcinomas. (5th November 2014) - Cheon, Dong‐Joo; Walts, Ann E; Beach, Jessica A; Lester, Jenny; Bomalaski, John S; Walsh, Christine S; Ruprecht Wiedemeyer, W; Karlan, Beth Y; Orsulic, Sandra
Abstract The current standard of care for epithelial ovarian cancer does not discriminate between different histologic subtypes (serous, clear cell, endometrioid and mucinous) despite the knowledge that ovarian carcinoma subtypes do not respond uniformly to conventional platinum/taxane‐based chemotherapy. Exploiting addictions and vulnerabilities in cancers with distinguishable molecular features presents an opportunity to develop individualized therapies that may be more effective than the current 'one size fits all' approach. One such opportunity is arginine depletion therapy with pegylated arginine deiminase, which has shown promise in several cancer types that exhibit low levels of argininosuccinate synthetase including hepatocellular and prostate carcinoma and melanoma. Based on the high levels of argininosuccinate synthetase previously observed in ovarian cancers, these tumours have been considered unlikely candidates for arginine depletion therapy. However, argininosuccinate synthetase levels have not been evaluated in the individual histologic subtypes of ovarian carcinoma. The current study is the first to examine the expression of argininosuccinate synthetase at the mRNA and protein levels in large cohorts of primary and recurrent ovarian carcinomas and ovarian cancer cell lines. We show that the normal fallopian tube fimbria and the majority of primary high‐grade and low‐grade serous ovarian carcinomas express high levels of argininosuccinate synthetase, which tend to further increase in recurrent tumours. In contrast to the serous subtype, non‐serous ovarian carcinoma subtypes (clear cell, endometrioid and mucinous) frequently lack detectable argininosuccinate synthetase expression. The in vitro sensitivity of ovarian cancer cell lines to arginine depletion with pegylated arginine deiminase was inversely correlated with argininosuccinate synthetase expression. Our data suggest that the majority of serous ovarian carcinomas are not susceptible to therapeutic intervention with arginine deiminase while a subset of non‐serous ovarian carcinoma subtypes are auxotrophic for arginine and should be considered for clinical trials with pegylated arginine deiminase.